Oligoene and cyanine features of tetracyano quinoidal oligothiophenes - Moles Quintero, Sergio; Zafra-Paredes, Jose Luis; Yamamoto, Keitaro; Aso, Yoshio; Ie, Yutaka; Casado-Cordón, Juan (Royal Society of Chemistry, 2021)
This paper interprets a palette of spectroscopic data on tetracyano thienoquinoidal molecules of different sizes oriented towards the elucidation of their electronic behavior and other aspects of interest in materials chemistry. It also provides a contextualization of these properties between those of even oligoenes (carotene-like) and those of odd cyanines as a function of the reduction state. A complete UV-Vis-NIR electronic absorption, fluorescence emission and infrared spectroscopic study in part helped by quantum chemical calculations in the framework of the DFT theory has been carried out. The study encompasses the neutral and charged states. The optical properties of these compounds in the neutral state are controlled by the competition of bright (electric dipole–dipole allowed) and dark (electric dipole–dipole forbidden) singlet excited states. In the anionic state, the trimeric compounds disclose behaviors compatible with being either charge localized or delocalized mixed valence systems. Interestingly, we show the π-dimerization of a radical anion of a thienoquinoidal compound forming a π-dimer dianion as a manifestation of the delocalization of the charge in the charged monomer. The hexamer compound in the neutral state discloses incipient diradical character which permits the detection of a NIR emission band from the dark state at energies well below 1 eV. As thiophene benzo-annulation minimizes the diradical character, it forces the confinement of the charge in the vicinity of the terminal dicyanomethylene groups in the dianion. The oxidized species of the compounds have been also analyzed as models of charge localization states. The competition between doublet and quartet high spin states in the radical cations has been explored with the objective of visualizing potential molecules able to produce SOMO–HOMO energy inversion. (...)
Keywords: Espectroscopía; Oligoene; Cyanine; Tetracyano quinoidal oligothiophenes